Sosialisasi Pencegahan dan Pemberantasan Demam Berdarah Dengue (DBD) pada Anak di TK Islam Al-Adaby 2 Pontianak Timur - Wahyuni, Tri; Kardiatun, Tutur; Ariyanti, Sri (Indra Institute Research & Publication, 2024)
DBD (Dengue Hemorrhagic Fever) is an infectious disease caused by the Aedes aegypti mosquito. DHF cases in the Pontianak area are also quite high, although they have decreased compared to previous years. Various efforts have been made to control dengue fever, until now it can be said that dengue fever is still an epidemic in Indonesia, including the city of Pontianak. The aim of this program is to socialize to the community at Al-Adaby Islamic Kindergarten about how to prevent and eradicate dengue fever in the environment. Method used in the form of interactive counseling, demonstration and evaluation. The appropriate method for preventing dengue fever is by eradicating mosquito nests (PSN) through 3 M (Draining, Covering, Burying) and sowing larvicide and spreading fish in water reservoirs, and other activities that can prevent/eradicate Aedes mosquitoes from breeding. It is hoped that the community will be able to understand the dengue epidemic and how to control and eradicate dengue fever